A rare case of small cell carcinoma of lung with intraventricular metastasis. (4th May 2019) - Chen, Hao; Raza, Hafiz Khuram; Shi, Hongjuan; Zhu, Jienan; Cui, Guiyun
Abstract: Our case report involves a Chinese patient who was presented to our hospital with the chief complaint of dizziness and double vision for one week. He was diagnosed with small cell carcinoma of lung in the past. The patient undertook various test at our hospital. His MR scan revealed an intraventricular metastasis from small cell carcinoma of lung which is very rare. We have analyzed the clinical data of this patient and related literature. We report this case to increase the awareness of this rare metastasis of small cell carcinoma of lung.